Occupational stress of physicians and nurses in emergency departments after contracting COVID-19 and its influencing factors: a cross-sectional study - Lv, Chuanzhu; Gan, Yong; Feng, Jing; Yan, Shijiao; He, Heyu; Han, Xiaotong (Frontiers in Public Health, 2023)
Background: Occupational stress is one of the major occupational health hazards globally. This study investigated the current situation of and factors influencing the occupational stress of physicians and nurses in emergency departments (EDs) after contracting coronavirus disease (COVID-19). Methods: An online questionnaire survey was conducted among physicians and nurses in EDs in China between January 5 and 8, 2023. A general descriptive analysis of variables was conducted, the differences in the occupational stress of physicians and nurses in EDs with different characteristics were analyzed using the chi-square test, and factors influencing occupational stress were investigated using generalized ordinal logistic regression. Results: Of the 1924 physicians and nurses in EDs who contracted COVID-19, 64.71% considered their occupational stress high or very high, with overly intense work as the primary stressor. Those with ≥ 10 years of work tenure, working in tertiary hospitals and with higher professional titles were more stressed, while females, nurses, those with a master’s degrees or higher, and those who continued to work after contracting COVID-19 were less stressed. There were differences in the predictors of occupational stress between physicians and nurses. Conclusions: China’s physicians and nurses in EDs had high occupational stress after contracting COVID-19. Attention should be given to the occupational mental health of physicians and nurses in EDs, and training on the prevention and treatment of COVID-19 infection should be strengthened.